Ebenezer Sage correspondence - Sage, Ebenezer, 1755-1834.
ALS (1810 January 24) from Sage to his niece describing the weekly levees given by Dolley Madison including reception protocol, refreshments, and the decor of the White House rooms. Other topics include U.S. relations with Great Britain and France and Sage family affairs. Includes a typewritten transcript of the letter.
U.S. representative and physician from New York.
Collection material in English.
Keywords: Madison, Dolley, -- 1768-1849.; Sage family; White House (Washington, D.C.); France -- Foreign relations -- United States; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- France; United States -- Foreign relations -- Great Britain; Washington (D.C.) -- Social life and customs; Physicians; Representatives, U.S. Congress -- New York (State)